Cellular Respiration of Acetic Acid Bacteria: Oxidative Fermentation and Applications - พงษ์ดำ ดร.ศยามพงษ์ (Journal of Food Health and Bioenvironmental Science, 2017)
Acetic acid bacteria are aerobic bacteria, classified as the Acetobacteraceae family. During oxidative fermentations, they can oxidize many organic compounds, such as ethanol, sugars, sugar alcohols and organic acids. The main oxidative enzymes are alcohol dehydrogenase, aldehyde dehydrogenase, alcohol-aldehyde dehydrogenase, gluconate dehydrogenase and polyol-dehydrogenase. In oxidative fermentation applications, the important products are acetic acid, dihydroxyacetone, L-sorbose, cellulose and gluconic acid, and applications of the products are pharmaceuticals, cosmetics, food industry, agriculture, chemical industry and textile industry. Nowadays, there are many researches and developments for improvement of acetic acid bacteria fermentations. Researches are based on bacterial cellular respiration, substrate oxidation, and oxidative enzymes. The development of oxidative fermentation can be applied in microbiology, biotechnology, manufacturing processes and biochemical engineering.